2022
DOI: 10.3390/bios12020086
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Single Fe-Based Nanoagents for Photothermal–Chemodynamic Cancer Therapy

Abstract: Monomodal cancer therapies are often unsatisfactory, leading to suboptimal treatment effects that result in either an inability to stop growth and metastasis or prevent relapse. Thus, synergistic strategies that combine different therapeutic modalities to improve performance have become the new research trend. In this regard, the integration of photothermal therapy (PTT) with chemodynamic therapy (CDT), especially PTT/CDT in the second near-infrared (NIR-II) biowindow, has been demonstrated to be a highly effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…CDT/PTT has demonstrated to be highly effective and relatively safe, and it can directly ablate cancer cells as well. Additionally, photothermal effects during PTT can speed up the Fenton-based process’ reaction rate and enhance CDT ( Yu et al, 2021 ; Zhang et al, 2022 ). With the development of nanotechnology, various targeted and multifunctional nanoparticles have been reported, which can deliver drugs and directly or indirectly activate the immune system to kill cancer cells ( Hooftman and O'Neill, 2022 ; Luo et al, 2021 ; Sun et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…CDT/PTT has demonstrated to be highly effective and relatively safe, and it can directly ablate cancer cells as well. Additionally, photothermal effects during PTT can speed up the Fenton-based process’ reaction rate and enhance CDT ( Yu et al, 2021 ; Zhang et al, 2022 ). With the development of nanotechnology, various targeted and multifunctional nanoparticles have been reported, which can deliver drugs and directly or indirectly activate the immune system to kill cancer cells ( Hooftman and O'Neill, 2022 ; Luo et al, 2021 ; Sun et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…CuFeSe 2 NCs have also been used for PTT. [ 129,130 ] Jiang et al. reported the highest photothermal conversion efficiencies so far, 82%, with 5 nm CuFeSe 2 nanoparticles.…”
Section: Applicationsmentioning
confidence: 99%
“…CuFeSe 2 NCs have also been used for PTT. [129,130] Jiang et al reported the highest photothermal conversion efficiencies so far, 82%, with 5 nm CuFeSe 2 nanoparticles. For an example, Figure 9e compares the CT images and X-ray attenuation of [127] Copyright 2017, The Royal Society of Chemistry.…”
Section: Photothermal Propertiesmentioning
confidence: 99%
“…Before precisely designing a Fenton/ Fenton-like reaction-based nanomedicine, it is important to take into account the feasibility of active redox cycles in the pH state, catalyst loading, and stability of oxidation products. Te full potential of chemodynamic cancer therapy is frequently limited by the intricacy of TME and the preparation of an "all-in-one" chemodynamic drug [124]. Designing appropriate Fenton nanosystems and modifying TME in favour of CDT is therefore of utmost importance.…”
Section: Fenton-reaction Approachmentioning
confidence: 99%